User’s evaluation about quality of the service in emergency care unit - Seleghim, Maycon Rogério; Teixeira, Jéssica Adrielle; Matsuda, Laura Misue; Inoue, Kelly Cristina (Rev Rene, 2010)
This study aimed at evaluating under the users view, the quality structure and quality process of some services in an Emergency Care Unit of a university hospital. Fifty-fi ve clients/users took part in the survey when they were admitted in the unit and were waiting for an examination. Data were collected from December 2007 to March 2008, using a questionnaire and treated in the structure and process categories, increased of the Positivity Index (PI) for each sub item and average Positivity Index for each item/service. The items to which was given higher PI were the conditions of cleaning, feeding and safety regarding medical care and nursing; the lower PI was attributed to the physical space, number of workers and communication/interaction between customers and professionals. It was concluded, in the overall aspects that, the quality of services obtained a ‘Satisfactory’ level, however, to reach the “Excellent” quality (highest quality aspects of the structure and workers’ performance), must be improved.